Well-being of Women in New Zealand: The Changing Landscape - Jessica Dye; Stephanie Rossouw; Gail Pacheco (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2012)
As the first country to give women the right to vote in 1893, New Zealand (NZ) has often been viewed as a leader in the global movement towards gender equality. This paper aims to assess trends in overall well-being for NZ women, by pulling together a range of statistical indicators across five key facets of well-being: demographic and family changes, education, employment, health, and crime and violence. From our analysis two contrasting pictures emerge. The first is that NZ women are clearly making up ground in respect of their education, participation in the labour force (less so in terms of wage equality), and overall health outcomes (barring mental health issues, such as depression). In the second, however, NZ women are trailing behind their other developed nation counterparts when one considers crime and violence, both committed against and by them.
Keywords: I10; J10; 330; Gender equality; women's well-being